2022
DOI: 10.1002/ctm2.862
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel therapeutic target underlying atypical manifestation of Gaucher disease

Abstract: Dear Editor,In the present study, we delineate the molecular pathways underlying atypical progressions of Gaucher disease (GD) that lead to unresponsiveness to enzyme replacement therapy (ERT). Specifically, we observed the accumulation of dense substrates (e.g., glucosylsphingosine [Lyso-Gb1]), which was associated with alterations in complement activity, autophagy metabolism, macrophage polarization and TGF-β signaling and subsequent endothelialto-mesenchymal transition (EndMT) and fibrosis. We also describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These events have been linked to the development of severe and chronic brain inflammation, resulting in the loss of neurons and early death [ 78 , 92 , 93 , 95 , 96 , 97 , 98 , 99 , 100 ]. Recent studies using induced pluripotent stem cell (iPSC)-derived mϕs and lymph nodes from patients with type 2 and type 3 Gaucher diseases have demonstrated that the C5a-C5aR1 axis triggers the induction of TNFα and TGFβ signaling [ 101 , 102 ]. The observed events, such as the induction of TNFα and TGFβ signaling triggered by the C5a-C5aR1 axis, have the potential to cause significant harm to patients with neuronopathic Gaucher disease.…”
Section: Gaucher-disease-associated Neuroinflammation: Deciphering Th...mentioning
confidence: 99%
“…These events have been linked to the development of severe and chronic brain inflammation, resulting in the loss of neurons and early death [ 78 , 92 , 93 , 95 , 96 , 97 , 98 , 99 , 100 ]. Recent studies using induced pluripotent stem cell (iPSC)-derived mϕs and lymph nodes from patients with type 2 and type 3 Gaucher diseases have demonstrated that the C5a-C5aR1 axis triggers the induction of TNFα and TGFβ signaling [ 101 , 102 ]. The observed events, such as the induction of TNFα and TGFβ signaling triggered by the C5a-C5aR1 axis, have the potential to cause significant harm to patients with neuronopathic Gaucher disease.…”
Section: Gaucher-disease-associated Neuroinflammation: Deciphering Th...mentioning
confidence: 99%
“…Even though GD1 is considered non-neuropathic, it has been shown that these patients are in a higher risk of developing Parkinson’s disease (PD) [ 3 , 4 ]. GD treatment includes enzyme-replacement therapy (ERT) and substrate-reduction therapy (SRT) that offers a significant improvement for most clinical parameters, with the exception of neurological impairment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, lyso-Gb1 has demonstrated its accessibility in clinical samples, quantifiability in an easy and reliable manner, and significant value both as a diagnostic tool and as an indicator of responses to therapeutic interventions [ 1 , 9 ]. Despite enzyme-replacement therapy (ERT), most GD2/3 patients, as well as some GD1 patients, have atypical manifestations such as lymphadenopathy, multiple myeloma, lymphoma, and neurotoxicity [ 1 , 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that atypical cells in patients with GD activate the classical pathway of complement, and ambroxol helps prevent endothelial-to-mesenchymal transition by stabilizing TGF-β signaling. 6 Ongoing real-world trials with high-dose ambroxol in GD, considering different types and treatment states, show no severe adverse events. Patients, even those with poor response to ERT, show improved symptoms and halted neurological decline with ambroxol treatment.…”
mentioning
confidence: 98%